Exploring the community energy actions to alleviate energy poverty in the Greek context - Konstantopoulos, Georgios; Kanellou, Eleni; Kontogiannis, Konstantinos (Technical Annals, 2023)
Energy poverty is a significant problem in Greece, affecting many people and exacerbating social inequality. Lack of access to affordable and reliable energy negatively impacts health, comfort, and economic opportunities, with long-term consequences for communities. While various initiatives have been implemented to address energy poverty, energy communities are emerging as a promising approach to tackle this issue. Energy communities refer to groups of people who come together to produce, consume, and manage their energy resources collectively. They enable households and communities to reduce their energy bills, improve living conditions, and enhance social and economic resilience. Energy communities can also stimulate local development and promote renewable energy technologies, contributing to a more sustainable and equitable energy system. This paper reviews energy poverty alleviation actions by community energy initiatives across Europe, identifies best practices and challenges, and proposes relevant energy poverty alleviation actions for energy communities in Greece. The paper seeks to contribute to the ongoing debate on how energy communities can contribute in energy poverty alleviation.